2021
DOI: 10.1080/21655979.2021.2009415
|View full text |Cite
|
Sign up to set email alerts
|

Fluvastatin suppresses the proliferation, invasion, and migration and promotes the apoptosis of endometrial cancer cells by upregulating Sirtuin 6 (SIRT6)

Abstract: Fluvastatin, the first fully synthesized 3-Hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase (HMGCR) inhibitor, has been reported to inhibit the development and metastasis of multiple cancers. The present study aimed to explore the effects of fluvastatin on endometrial cancer (EC) as well as reveal its potential mechanism. After exposure to fluvastatin, the cell viability, proliferation, migration, and invasion of EC cells were measured by Cell Counting Kit-8 (CCK-8), 5-ethynyl-2ʹ-deoxyuridine (EDU), wou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…Although the inhibitory effects of fluvastatin have been shown in various cancers, the underlying molecular mechanisms are not well understood and complex, including Sirtuin 6 upregulation, HMG-CoA reductase inhibition, Ras isoprenylation and inhibition of Akt phosphorylation. 13,31,32 Similar to atorvastatin’s action in glioblastoma, 14 our mechanistic studies confirm that fluvastatin acts on glioblastoma via suppressing Ras activity, and furthermore that this is prenylation-dependent. Aberrant Ras activation due to either overexpression or mutation plays a pivotal role in regulating proliferation, survival, differentiation and signal transduction in glioblastoma.…”
Section: Discussionsupporting
confidence: 61%
“…Although the inhibitory effects of fluvastatin have been shown in various cancers, the underlying molecular mechanisms are not well understood and complex, including Sirtuin 6 upregulation, HMG-CoA reductase inhibition, Ras isoprenylation and inhibition of Akt phosphorylation. 13,31,32 Similar to atorvastatin’s action in glioblastoma, 14 our mechanistic studies confirm that fluvastatin acts on glioblastoma via suppressing Ras activity, and furthermore that this is prenylation-dependent. Aberrant Ras activation due to either overexpression or mutation plays a pivotal role in regulating proliferation, survival, differentiation and signal transduction in glioblastoma.…”
Section: Discussionsupporting
confidence: 61%
“…Glucose availability–specifically, high glucose-mediated increases in reactive oxygen species–has been shown to influence cNCC apoptosis 9 . Furthermore, studies have shown both fatostatin and fluvastatin, a direct inhibitor of HMG-CoA reductase, to possess apoptotic effects 30 33 . We were therefore interested in examining the effect of cholesterol inhibitors on cNCC susceptibility to apoptosis under varying glucose conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Fluvastatin, the first fully synthetic HMG-CoA reductase (HMGCR) inhibitor, is reported to prevent the growth and spread of certain malignancies ( Cai and Zhao, 2021 ). Fluvastatin prevents trained immunity by downregulating H3K4me3 and blocking the production of proinflammatory cytokines ( Arts et al, 2016a ).…”
Section: Inhibitors Of Targeting Trained Immunitymentioning
confidence: 99%